Clinical profile and practice patterns of patients with severe hypercholesterolemia: A Hospital-based registry - Adhikari, Chandra Mani; Bogati, Amrit; Timilsena, Birat Krishna; Khan, Barkadin; Kharel, Sushant; Safi, Sajjad; Ghimire, Vijay; Adhikari, Puja; Thapa, Pratik; Prajapati, Dipanker (Nepalese Heart Journal, 2024)
Background Severe Hypercholesterolemia, defined as low-density lipoprotein cholesterol of ≥190mg/dL (≥4.9 mmol/L), has a high risk of Atherosclerotic Cardiovascular Disease and premature and recurrent coronary events. Its prevalence may be as high as 5–7% in the general population. This registry aims to provide insights into clinical profiles and practice patterns among such patients treated at the tertiary cardiac hospital of Nepal. Methods This was a cross-sectional, observational, registry of the patients who were diagnosed with Severe Hypercholesterolemia from January 2022 to December 2022 in the Shahid Gangalal Heart Centre. Results: In this registry, 119 cases were included. The mean age of patients was 53± years with 56.3% female patients. 74 (62.1%) were hypertensive,16 (13.4%) had Diabetes mellitus, and 16(13.4%) patients were consuming tobacco. History of premature coronary artery disease was present in 15 (12.6%) patients, a history of premature peripheral vascular disease in 1(0.8%) patient, a family history of premature coronary artery disease was present in 4 (3.3%), and family history of total cholesterol level of >7.5mmol/L was present in 20 (16.8%), tendon xanthoma in 4 (3.3%) cases, arcus cornealis in 22 (18.4%) cases. Body mass index ranged from 15.2 to 43.2 with a mean of 26.3. More than 60% of cases were overweight, or obese. Rosuvastatin was used in 87 (73.1%) cases and atorvastatin in 32 (26.9%) cases. Ezetimibe 10 mg combined with atorvastatin in 18(15.1%) cases. In 93 (78.1%) cases were treated with high doses of statin. Conclusion: Severe Hypercholesterolemia hospital-based registry provides valuable information on Severe Hypercholesterolemia regarding the associated cardiovascular risk factors and its clinical presentation. Most of the patients were treated with high doses of statins as recommended by guidelines.